Ab initio molecular dynamics prediction and experimental validation of the 14:4 rare-earth oxide-phosphate structure - Qi-Jun Hong; Sergey V. Ushakov; Ligen Wang; Konrad Burkmann; Jared Matteucci; Jun Wu; Andrew Fitch; Chathuranga S. Witharamage; Hongwu Xu; Elizabeth J. Opila; Robert Glaum; Alexandra Navrotsky (Proceedings of the National Academy of Sciences, 2026)
Rare-earth oxide-phosphates (historically termed oxyphosphates) occupy the compositional space between RE 2 O 3 and REPO 4 and form during REPO 4 melting and high-temperature degradation of REPO 4 -based environmental barrier coatings. For several reported stoichiometries, reliable structural models remain unavailable because these phases are low-symmetry, large–unit-cell compounds that seldom form crystals suitable for single-crystal X-ray diffraction. Here, we predict the crystal structure of the compounds reported in the literature as “RE 8 P 2 O 17 ” (RE: Sm to Lu, Y) by combining finite-temperature ab initio molecular dynamics (AIMD) simulations with targeted experiments. Syntheses and electron microprobe analysis show the correct RE:P ratio is 3.5, corresponding to RE 14 P 4 O 31 (14:4). Starting from the melt, AIMD simulations in the SLUSCHI framework, followed by symmetry-constrained relaxation, yield a complex (62 distinct oxygen sites on general positions), monoclinic Pc structure which represents a hitherto unknown structure type. It can be described as a defect fluorite (bixbyite, C -type RE 2 O 3 ) structure penetrated along one direction by tunnels containing (PO 4 ) tetrahedra. The structure was initially predicted for Y 14 O 15 (PO 4 ) 4 and was validated for RE = Sm, Eu, Gd, Tb, and Y against synchrotron or laboratory X-ray powder diffraction patterns. Extending the model across the rare-earth series yields consistent lattice trends and places all oxide-phosphates RE 14 O 15 (PO 4 ) 4 within 46 meV/atom of the 0 K convex hull. A finite-temperature free-energy analysis from MD trajectories predicts entropy stabilization of Y 14 O 15 (PO 4 ) 4 above ~1,305 K, reconciling metastability at 0 K with observed synthesis and helping resolve discrepancies among published Y 2 O 3 –YPO 4 phase diagrams.